2001
DOI: 10.1111/j.1740-8261.2001.tb00970.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Combination of Medetomidine‐butorphanol and Medetomidine, Butorphanol, Atropine on Glomerular Filtration Rate in Dogs

Abstract: The effects of intramuscularly administered medetomidine and butorphanol (MB), and medetomidine, butorphanol, atropine (MBA) on glomerular filtration rate (GFR) were determined in six dogs as measured by 99m-Tc-labeled diethylenetriaminepentaacetic acid (99mTc-DTPA) nuclear scintigraphy. Direct systolic, diastolic, and mean arterial blood pressures and heart rate were measured at regular time intervals before, during, and after GFR calculations. The mean GFR measurement following MB was significantly greater (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
1
17
0
3
Order By: Relevance
“…The observed major effects of anesthesia on renal functions have been reported to be due to indirect circulatory and neuroendocrine responses [4,12]. Alpha 2 -adrenoceptor agonists have been shown to have many advantages desired in anesthetic, which include sedation, analgesia and muscle relaxation [14,15,26], however, previous studies have demonstrated the ability of these drugs to alter hemodynamic, initially they rise mean arterial blood pressure (MABP) due to their effects on postsynaptic α 2 -adrenoceptors with the resultant increase in systemic vascular resistance [27], this is followed by long-lasting decrease due to stimulation of central and peripheral presynaptic α 2 -adrenoceptors, therefore decrease sympathetic outflow and reduce cardiac output.…”
mentioning
confidence: 99%
“…The observed major effects of anesthesia on renal functions have been reported to be due to indirect circulatory and neuroendocrine responses [4,12]. Alpha 2 -adrenoceptor agonists have been shown to have many advantages desired in anesthetic, which include sedation, analgesia and muscle relaxation [14,15,26], however, previous studies have demonstrated the ability of these drugs to alter hemodynamic, initially they rise mean arterial blood pressure (MABP) due to their effects on postsynaptic α 2 -adrenoceptors with the resultant increase in systemic vascular resistance [27], this is followed by long-lasting decrease due to stimulation of central and peripheral presynaptic α 2 -adrenoceptors, therefore decrease sympathetic outflow and reduce cardiac output.…”
mentioning
confidence: 99%
“…Administration of medetomidine 50 µg/kg, IV decreases renal uptake of technetium 99m-labeled diethylenetriamine pentaacetic acid ( 99m Tc-DTPA) for 15 min after administration in dogs [12] and 10 µg/kg, IV of dexmedetomidine decreased renal blood flow by 30% in dogs anesthetized with chloralose and urethane or fentanyl and halothane [23]. In contrast, medetomidine (11 µg/kg, IV) administered with butorphanol (0.22 mg/kg, IV) increased GFR in dogs [15]. In human thoracotomy patients, administration of a dexmedetomidine infusion was shown to enhance renal function, including indices of glomerular filtration as well as urine flow rate [10].…”
Section: Discussionmentioning
confidence: 99%
“…[90][91][92] Some drug combinations commonly used in veterinary medicine have been shown to increase GFR, thought to be due to constriction of efferent arterioles resulting in increased glomerular hydrostatic pressure. 92 In cases of systemic hypotension resulting from sedative administration, GFR is usually sustained at normal levels by maintenance of renal blood flow. 90,91 Animals studied by Gahring et al 13 were anesthetized with thiamylal sodium and maintained with methoxyflurane and oxygen.…”
Section: C: Discussionmentioning
confidence: 99%